A Question of Demand and Supply? Defining the Demand and Providing a Supply of Respirologists. Issue 6 (3rd December 2000) - Jones, Norman L
Abstract : In this issue of the Canadian Respiratory Journal, we are invited to think about respirology manpower in Canada. I believe it is the first time that the Journal has published on the topic, perhaps suprisingly, for the issues that are raised are of great importance to all physicians who care for patients with chest problems. Dr Don Cockcroft and Dr David Wensley (pages 451-455) conducted a survey of program directors and obtained data regarding Royal College Fellows, which allowed them to estimate the number of chest specialists currently in practice and to predict what will happen to these numbers in the foreseeable future. Based on the numbers and the waiting times for outpatient appointments, their main conclusions are that there is a shortfall in adult respirologists that may be as high as 50%; that the shortfall is at least as large for pediatric specialists; and that current output from training programs is unlikely to meet the shortfalls. Currently, they estimate a total of 361 adult specialists, or one for every 86, 000 population, but with regional differences that account for a variation from one to 69, 000 in Alberta to one to 253, 000 in New Brunswick.